Artikel Tinjauan: Sediaan Ekstrak Daun Kelor (Moringa oleifera L.) dalam Menurunkan Kadar Glukosa Darah pada Tikus (Rattus norvegicus) yang diinduksi Aloksan - Biandra Cinta Ramadhani; Dia Septiani; Gita Novianti Lismawana; Hanifah Nur Widodo (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
This study aims to evaluate the effectiveness of Moringa oleifera L. leaf extract preparations in lowering blood glucose levels in alloxan-induced white rats (Rattus norvegicus) through a Systematic Literature Review (SLR) approach. The review process followed the PRISMA 2020 guidelines, with a literature search conducted on the PubMed, ScienceDirect, and Google Scholar databases for the 2015–2025 period. Out of 472 identified articles, nine studies met the inclusion and exclusion criteria for further analysis.The review results indicate that all studies reported a significant decrease in blood glucose levels after the administration of Moringa oleifera leaf extract, both in the form of water extract and ethanol extract. The effective dose used ranged from 200–800 mg/kg body weight, with the highest effectiveness observed at doses of 400–450 mg/kg and an administration duration of 14–28 days. The water extract provided a faster glucose-lowering effect, while the ethanol extract showed more stable and longer-lasting results.The anti-hyperglycemic mechanism of Moringa oleifera leaf extract includes the stimulation of insulin secretion, the protection of pancreatic β-cells against oxidative stress, and the enhancement of insulin sensitivity in target tissues. The content of flavonoids, saponins, tannins, and chlorogenic acid plays a crucial role in regulating glucose metabolism and increasing antioxidant activity. Overall, this review confirms that Moringa oleifera L. has strong potential as a candidate for a safe and effective natural anti-diabetic phytopharmaca. However, further research with standardized extraction methods and in-depth molecular analysis is still needed to strengthen the scientific basis for its utilization.